INVESTIGATION OF SELF-REGULATED LEARNING IN GRADE 6 STUDENTS OF A PUBLIC PRIMARY SCHOOL IN SINGARAJA IN TEACHING-LEARNING PROCESS - Widiadharma, Gede Krisna; Tresnayanti, Ni Putu Desi; Pradnyani, Ni Putu Prami; Santosa, Made Hery; Rewa, Gde Arys Bayu (Jurnal Pendidikan Bahasa Inggris Proficiency, 2025)
This study investigates the implementation of Self-Regulated Learning (SRL) in a sixth-grade classroom at a public primary school in Singaraja. Employing a qualitative case study approach, data were collected through classroom observations and semi-structured interviews with teachers and students. The findings reveal that SRL strategies, including goal setting, self-monitoring, and self-reflection, empower students to become active participants in their education. Teachers played a vital role in fostering these practices through scaffolding and guidance, while group activities promoted collaboration and critical thinking. Independent material selection was observed to enhance engagement, critical thinking, and digital literacy, aligning with modern educational frameworks like Indonesia’s Merdeka Belajar initiative. However, challenges such as varying levels of student readiness, limited research skills, and insufficient familiarity with digital tools were noted, highlighting the need for structured teacher support. The study emphasizes the importance of balancing independence and guidance to maximize SRL’s benefits, preparing students for lifelong learning and adaptability in dynamic educational contexts.